Sonographers' experiences of being a caring professional within private practice in the province of Gauteng - Leah van der Westhuizen; Kathleen Naidoo; Yasmin Casmod; Sibusiso Mdlethse (AOSIS, 2020)
Background: Medical imaging has been driven by technological advancements. However, the concept of caring has now become a significant element in the healthcare profession. Within a South African context, there are principles that emphasise the importance of people and service delivery: the Batho Pele Principles and Ubuntu. Now more than ever, there is a greater need for a patient-centred caring environment. Therefore, there is an expectation for sonographers to be adaptive to this new environment. Aim: The purpose of this study was to explore and describe the sonographers' experiences of being caring professionals. Setting: Sonographers who work within private practices in Gauteng were part of this study. Methods: A qualitative, exploratory, descriptive, contextual, phenomenological research design was used. Focus group interviews were conducted with qualified sonographers registered with the HPCSA. Thematic analysis was used to code data into themes and categories. Results: Four themes emerged: the effects of a caring relationship between a sonographer and a patient; circumstances limiting a sonographer in being a caring professional; sonographers' approach to caring; educational readiness of sonographers to be caring professionals. Conclusion: The participants in this study explained and shared their understanding of being caring professionals. They shared many stories regarding trusting relationships with patients. However, as a caring professional, many challenges were encountered, both physically and emotionally. Recommendations such as reflective journals and the practices of Jean Watson's theory of transpersonal caring are cited to focus on the practice and education that may improve caring among sonographers.